A (res)significação da produção escrita através do relato pessoal - Moura, Priscila Mendonça (2019)
The present study analyzed the textual productions of a 6th grade class, Elementary School II, from a state public school of Santo Amaro das Brotas, in search of strategies to resignify written production through the development of the social - emotional abilities of students, that is, through the strengthening of self-esteem and identity, as an alternative in combating the cycle of failures in the public school. Guided by qualitative research, we developed action research through a didactic sequence developed in seven stages, having as product an educational book. The personal reporting genre was the main instrument for data collection and intervention. The theoretical contribution of this study was based on the study of Abed's (1996, 2016) socio-emotional abilities; of the socio-historical and dialogical conception proposed by Bakhtin (2003) in consonance with the sociodiscursive interactionism of Bronckart (1999); Soares (2003, 2007, 2016), Rojo (2009), Kleiman (2010) and Cosson (2016) were used as reference for literacy theories; Marcuschi (2002, 2003) to deal with textual genres; Leffa (1996), Solé (1998), Oliveira (2010) and Borba (2013, 2014) to deal with aspects of reading and writing; Passarelli (2012) and Geraldi (2012) regarding the teaching of textual production; Perrenoud (2000), Dolz, Noverraz and Schneuwly (2004) based the didactic sequence, Jung (2008) brought the concepts about symbols and archetypes; Campbel (2008) and Vogler (2015) were used to approach the hero's journey. The analysis of the application showed that the didactic sequence provided reflection on the identity and the purpose of life, some students extended their personal reports during the procedural writing, with a positive perception of themselves, in addition to effectively providing the link between peers education.